(untitled) (CAHIERS MAGELLANES-NS, 2024)
Environmental loads are a set of direct and indirect impacts that occur as a result of human activities that put pressure on the natural environment. These loads include the consumption of natural resources such as energy and water, and the production of pollutants, heavy metals, and greenhouse gases that affect air, water, and soil quality, as well as ecosystems and human health. Environmental load management has become crucial to ensure resource sustainability and mitigate the effects of climate change. The research highlighted the environmental loads generated mainly from carbon dioxide (CO2) emissions and other pollutants resulting from the burning of fossil fuels during the operation of electric generators in urban areas. These emissions contribute to the phenomenon of global warming and negatively affect air quality and are recognized through the concept of carbon footprint, which is a measure of carbon emissions resulting from human activities, and is an essential part of environmental load analysis. The more generators are used in urban areas, the more carbon emissions they produce, and consequently the associated environmental loads increase. The carbon footprint of the activity of generating electricity using private generators was estimated by calculating the quantities of fuel consumed in this activity and factoring them with the emission factor. The carbon footprint of this activity amounted to 92,753.308 TCO2e annually, which is considered low compared to the transportation footprint or the footprint of electrical energy generated in power plants.